Cerebral Blood Flow Disorder in Acute Subdural Hematoma and Acute Intraoperative Brain Bulge - Xian, Liang; Wang, Cheng; Wei, Liangfeng; Wang, Shousen (Frontiers in Neurology, 2022)
Context Acute subdural hematoma (ASDH) has a high incidence and high mortality. During surgery for ASDH, brain tissue sometimes rapidly swells and protrudes into the bone window during or after removal of the hematoma. This phenomenon, known as acute intraoperative brain bulge, progresses rapidly and can cause ischemic necrosis of brain tissue or even mortality. The mechanism of this phenomenon remains unclear. Objective To investigate the changes in cerebral surface blood flow during ASDH and acute intraoperative brain bulge in rats. Methods Adult male Sprague–Dawley rats were selected to establish an ASDH model, and acute intraoperative brain bulge was induced by late-onset intracranial hematoma. The changes in cerebral surface blood flow during ASDH and acute intraoperative brain bulge were observed with a laser speckle imaging system, and intracranial pressure (ICP) was monitored. Results ICP in rats increased significantly after ASDH (P < 0.05). The blood perfusion rate (BPR) values of the superior sagittal sinus, collateral vein and artery decreased significantly in rats with subdural hematomas (P < 0.05). There was no significant difference between the preoperative and 90-min postoperative BPR values of rats. ICP was significantly increased in rats with acute intraoperative brain bulge (P < 0.05) and decreased significantly after the removal of delayed hematomas (P < 0.05). The BPR of the superior sagittal sinus, collateral vein and artery decreased significantly during brain bulge (P < 0.05). After the removal of delayed hematomas, BPR increased significantly, but it remained significantly different from the values measured before brain bulge (P < 0.05). Conclusion ASDH may cause not only high intracranial pressure but also cerebral blood circulation disorders. Brain bulge resulting from late-onset intracranial hematoma may aggravate these circulation disorders. If the cause of brain bulge in a given patient is late-onset intracranial hematoma, clinicians should promptly perform surgery to remove the hematoma and relieve circulation disorders, thus preventing more serious complications.